Liposomes as potential carriers for ketorolac ophthalmic delivery: formulation and stability issues - Mohammed Maher Mehanna; Nouran Abd El-Kader; Magda Wadih Samaha (Universidade de São Paulo, 2017)
ABSTRACT Drug delivery to treat ocular disorders locally is a challenging endeavor. Traditional ocular dosage form - eye drops - exhibits poor availability, consequently inefficient therapeutic response. The objective of the study was to formulate and characterize a ketorolac tromethamine ocular system with a prolonged release pattern based on liposomes as a vesicular carrier and to design once daily liquid preparation realizing the thermal in situ gelation principle. Liposomes were prepared by film hydration method. The influence of cholesterol concentration, pH and volume of hydration medium, and type and concentration of charging imparting agents were studied. Liposomes were characterized via, morphological examination, vesicular size, and encapsulation efficiency, and in vitro release performance, moreover its stability was assessed. The results obtained highlighted that liposomes showed a closed vesicular multi-lamellar structure. Ketorolac was successfully encapsulated within the liposomal structure in a cholesterol and charge inducing agent concentration-dependent behaviour. The dispersion of liposomes within thermosensitive Poloxamer in situ gel was able to retard the release of the drug by diffusion providing a controlled prolonged delivery. The liposomal formulations were physically stable for six months. Ketorolac tromethamine in situ liposomal gel representing an efficient alternative in terms of ocular retention and patient compliance when compared with conventional eye drops.